Extracting method knowledge elements from scientific literature: A rule‐based approach. Issue 1 (18th October 2019) - Wang, Zhongyi; Shen, Xueying; Huang, Rong; Huang, Jing
ABSTRACT: Knowledge elements are the basic unit of knowledge. Extracting knowledge elements from literatures enables granular knowledge organization and retrieval. This paper proposes a rule‐based framework for extracting method Knowledge Elements (KEs) in scientific literature aiming to improve the accuracy and complete extraction of method KEs. The method is divided into two stages: semi‐automated extraction of initial description rules of method KEs and automated derivation of additional description rules. In a preliminary evaluation on 415 papers, the precision and recall for the method KEs extraction are 0.77 and 0.84, respectively, indicating the effectiveness of our method.